The one-shot library instruction survival guide - Buchanan, Heidi E.; McDonough, Beth A. (ALA Editions, an imprint of the American Library Association, 2014)
Though many librarians want to be excellent teachers, they encounter significant barriers to their success, and formal preparation for teaching is usually not offered in graduate programs. To help your students become information literate, you must learn to turn everyday challenges into instruction that is meaningful and relevant for your students.